Flexible ZnO / CdS composite nano-film for photoelectric cathode protection as well as preparation method and application of flexible ZnO / CdS composite nano-film

Through the preparation of flexible ZnO/CdS composite nano films, the existing photocathode protection technology has been solved, and the protection effect and application of existing photocathode protection technology in marine atmospheric areas is limited, efficient photocathode protection for steel structures is achieved, and the limitations of traditional rigid photoanodes are broken, and suitable for a wide range of flexible applications.

CN119800368APending Publication Date: 2025-04-11WUHAN CORRTEST INSTR
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411987062.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing photocathode protection technology has limited protection effect on steel structures in marine atmospheric areas, and the application of traditional methods is limited by rigid conductive glass or metal surfaces, which cannot meet the needs of flexibility and widespread application.

Method used

A flexible ZnO/CdS composite nanofilm was prepared by combining a carbon cloth matrix, a ZnO nanolayer and a CdS nanolayer, using electrochemical deposition and SC-SILAR process, combined with the pretreatment technology of flexible carbon cloth, a flexible composite film with excellent photoelectric properties was prepared.

Benefits of technology

Effective photocathodic protection of coated steel structures is achieved, the potential drops below -1200 mV, which is significantly lower than the self-corrosion potential. It is characterized by low cost, simple preparation and excellent performance, and is suitable for a wide range of practical application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800368A_ABST
    Figure CN119800368A_ABST
Patent Text Reader

Abstract

The invention provides a flexible ZnO / CdS composite nano film for photoelectric cathode protection. The composite nano film sequentially comprises a carbon cloth substrate, a ZnO nano layer and a CdS nano layer, wherein the carbon cloth base body needs to be pretreated, specifically, the carbon cloth base body is soaked in a mixed solution of deionized water and absolute ethyl alcohol, then subjected to liquid-phase oxidation hydrophilic treatment and dried for standby application. The preparation method specifically comprises the following steps: firstly, depositing a ZnO nano layer on pretreated carbon cloth by utilizing electrochemistry, and then, depositing a CdS nano layer by utilizing a modified SILAR method (SC-SILAR), so as to obtain the flexible ZnO / CdS composite nano film. The light absorption range of the prepared flexible ZnO / CdS composite nano-film is expanded to a visible light region, and the flexible ZnO / CdS composite nano-film is soft in texture and suitable for different operation scenes, so that the potential of a protected coating steel electrode is reduced to-1200 mV or below and is obviously lower than the self-corrosion potential of the coating steel electrode, and the anti-corrosion effect is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite nano film preparation, and in particular relates to a flexible ZnO / CdS composite nano film for photoelectric cathode protection, and a preparation method and application thereof. Background Art

[0002] The corrosion areas of steel structures in marine corrosion environments can be divided into atmospheric zone, splash zone, tidal zone, full immersion zone and sea mud zone. The atmospheric zone refers to the atmospheric zone above the splash zone of the sea surface and the coastal atmospheric zone. It is characterized by high air humidity and high salt content. There are fine salt particles on the metal surface exposed to the marine atmosphere. After absorbing moisture in the air, sea salt particles can easily form a liquid film on the metal surface, causing corrosion. This is particularly obvious when the temperature reaches the dew point during seasonal or diurnal changes. At the same time, the deposition of dust and microorganisms on the metal surface will enhance the corrosiveness of the environment. Therefore, the corrosion of metal structures by marine atmosphere is much more serious than that of inland atmosphere. At present, the main protection methods for steel structures in marine atmospheric zones are electrochemical cathodic protection and coating of anti-corrosion coatings. However, the traditional cathodic protection method cannot protect steel structures in the tidal zone and above because the current cannot reach the tidal zone or atmospheric zone. In addition, the anti-corrosion coating is easy to fall off and break after ultraviolet radiation and wind and wave scouring, thus losing its protection ability.

[0003] Photocathode protection, as a new, green, pollution-free and sustainable metal corrosion protection technology, has received widespread attention in recent years. It combines the photoelectric properties of semiconductors with the mechanism of cathodic protection, using sunlight to excite semiconductors to generate photogenerated electrons. The photoelectrons are transferred to the metal through an external circuit or a conductive medium on the metal surface, causing the metal to be cathodically polarized, thereby reducing the metal corrosion potential and being protected. Compared with traditional corrosion protection technologies, photocathode corrosion protection technology has many advantages. First, photocathode protection does not require an external power supply, but only requires light energy to drive it, which saves energy and is environmentally friendly. Secondly, the photoanode can provide photoelectrons for a long time under the action of sunlight without being consumed, and will not produce metal ions to cause secondary pollution to the environment. It is an environmentally friendly corrosion protection measure.

[0004] Based on this, patent CN109913859A invented a silicon (Si) doped titanium dioxide (TiO2) film and uniformly coated it on the surface of 304 stainless steel as a photocathode protection coating. Si doping into the TiO2 lattice caused lattice defects, thereby inhibiting the recombination of electrons and holes to a certain extent, but failed to effectively improve the light absorption efficiency. Patent CN111962083A invented a graphite phase carbon nitride @ graphene composite film photoanode for photocathode protection. The photoanode has excellent light absorption and photoelectron transmission capabilities, but can only polarize the potential of the coupled metal to about -0.5 V, and the protection range of the metal is limited. Patent CN109735847B invented AgInS2 / graphene / TiO2 nanocomposite film photoanode for photocathode protection of Q235 carbon steel. The photoanode exhibits excellent photocathode protection performance, but its preparation is complex and the cost is high. In addition, the current patent inventions for photocathode protection all prepare photoanode materials on rigid conductive glass or metal surfaces, which greatly limits their flexible application in practice. Summary of the invention

[0005] In view of this, the present invention provides a flexible ZnO / CdS composite nanofilm for photoelectric cathode protection, which can protect the photoelectric cathode of the coated steel structure and has a wider application scenario due to its flexibility.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A flexible ZnO / CdS composite nanofilm for photocathode protection, the composite nanofilm comprising a carbon cloth substrate, a ZnO nanolayer, and a CdS nanolayer; The carbon cloth substrate needs to be pretreated: first, it is soaked in a mixed solution of deionized water and anhydrous ethanol, then subjected to liquid phase oxidation hydrophilic treatment, and then dried for standby use.

[0007] Furthermore, the carbon cloth substrate has a thickness of 0.35-0.4 mm; The volume ratio of deionized water to anhydrous ethanol is 7:3, and the soaking time is 3-5 h; Liquid phase oxidation hydrophilic treatment steps: soak for 1 to 2 hours at 70 to 80°C in a mixed solution of nitric acid and sulfuric acid with a volume ratio of 3:1 and a mass fraction of 8% to 12%.

[0008] Furthermore, the ZnO nanolayer is prepared from a Zn(NO3)2 solution using an electrochemical deposition process.

[0009] Furthermore, the CdS nanolayer is prepared by using an SC-SILAR process with an ethanol solution A of Cd(CH3COO)2·2H2O as a cadmium source and a methanol solution B of Na2S·9H2O as a sulfur source.

[0010] The preparation method of the composite nanofilm comprises the following steps. The specific preparation process diagram is shown in Figure 1 : S1. Take Zn(NO3)2 solution, use the pretreated carbon cloth substrate as the working electrode, platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode for electrochemical deposition. After the deposition is completed, dry it to obtain a carbon cloth with a ZnO nanolayer deposited. The SEM image is shown in Figure 4 (a); S2. Place the carbon cloth with the ZnO nanolayer in the middle of the spin coater, apply ethanol solution A, dry it, then apply methanol solution B, dry it, and obtain a flexible ZnO / CdS composite nanofilm. Figure 4 (b).

[0011] In some embodiments, preferably, the concentration of the Zn(NO3)2 solution is 0.005~0.01 M, and the pH is 4.5~5; Electrochemical deposition process: first treat in constant current mode of -2 mA for 15 S, then deposit in constant potential mode of -1 V for 20~30 min, and the electrodeposition temperature is 60~80℃.

[0012] In some embodiments, preferably, the concentration of Cd(CH3COO)2·2H2O in the ethanol solution A in step S2 is 25-35 mM; the concentration of Na2S·9H2O in the methanol solution B is 25-35 mM.

[0013] In some embodiments, preferably, the spin coater has a rotation speed of 1500-2500 rpm; The drop-coating volume of ethanol solution A and methanol solution B was 80-120 μL, the drop-coating time was 25-35 s, and the drop-coating times were 2 times; The entire coating and drying process cycle is repeated 6 times.

[0014] In some embodiments, preferably, the drying conditions in step S1 are: temperature 60° C., time 2.5 to 3.5 h; The drying conditions in step S2 are the same for the two dryings: temperature 60°C, time 3-7 min.

[0015] Application of the above-mentioned flexible ZnO / CdS composite nanofilm in photocathode protection.

[0016] The working principle of the flexible ZnO / CdS composite nanofilm prepared by the present invention is as follows: when ZnO is sensitized by CdS nanoparticles, CdS is excited under light, and the electrons in the valence band absorb light energy and are excited to the conduction band. Due to the internal electric field created by the heterostructure between ZnO and CdS, the electrons are transferred to ZnO and then to the coated steel with a lower Fermi level, making the potential of the steel negative to its corrosion potential and protected; while the holes remain in the CdS nanoparticles and are used to oxidize the reducing substances in the solution. Therefore, the ZnO / CdS composite film can effectively improve the photocathode protection performance of metals (see the schematic diagram for the protection mechanism). Figure 2 ).

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The flexible ZnO / Bi2S3 composite film prepared by the present invention has the characteristics of low cost, simple preparation and excellent performance. The light absorption range is extended to the visible light region, and it is an excellent photoanode material. Using flexible carbon cloth as a substrate breaks through the disadvantages of traditional rigid photoanodes, and the prepared flexible photoanode is more suitable for actual conditions.

[0018] (2) When the composite film prepared by the present invention is irradiated with visible light, the potential of the coated steel electrode in the coupled corrosion electrolytic cell can be reduced to below -1200 mV, which is significantly lower than its self-corrosion potential (-230 mV); the photocurrent density generated after irradiation is 1400 μA / cm 2 about. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The figure is a schematic diagram of the process of preparing a flexible composite film according to the present invention.

[0020] Figure 2 Schematic diagram of the photocathode protection mechanism of the flexible composite film prepared in the present invention.

[0021] Figure 3 Schematic diagram of the flexible composite film photoelectric cathode protection performance testing device prepared by the present invention.

[0022] Figure 4 Scanning electron microscope images (SEM) of (a) ZnO thin film and (b) ZnO / CdS composite thin film prepared in the present invention.

[0023] Figure 5 The graph shows the coupling of 304 stainless steel and the ZnO / CdS composite film photoanode prepared in Example 1. The curves of potential and current density changing with time before and after illumination (≥420nm). Light represents illumination, and Dark represents turning off the light source, i.e., darkness.

[0024] Figure 6The photoanode coupling of 304 stainless steel and the ZnO / CdS composite film prepared in Comparative Example 2 is shown, and the curves of potential and current density changing with time before and after illumination (≥420nm). Light represents illumination, and Dark represents turning off the light source, i.e. darkness.

[0025] Figure 7 The photoanode coupling of 304 stainless steel and the ZnO / Bi2S3 composite film prepared in Comparative Example 3 is shown, and the curves of potential and current density changing with time before and after illumination (≥420nm). Light represents illumination, and Dark represents turning off the light source, i.e. darkness.

[0026] Figure 8 The photoanode coupling of 304 stainless steel and the ZnO / CdS composite film prepared in Comparative Example 4 is shown, and the curves of potential and current density changing with time before and after illumination (≥420nm). Light represents illumination, and Dark represents turning off the light source, i.e., darkness. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.

[0028] Example 1 This embodiment provides a flexible ZnO / CdS composite nanofilm for photocathode protection, and the specific preparation method is as follows: S1. Pretreatment of carbon cloth The carbon cloth with a thickness of 0.4 mm was cut into rectangular carbon cloth sheets of 20*10 mm, and then soaked in a mixed solution of deionized water and anhydrous ethanol with a volume ratio of 7:3 at 80°C for 3 h, and finally dried at 60°C. The dried carbon cloth was soaked in a mixed solution of 10% nitric acid and 10% sulfuric acid with a volume ratio of 3:1 at 80°C for 1 h to complete the carbon cloth pretreatment.

[0029] Preparation of S2 and ZnO thin films Take 60 mL of 0.01 M Zn(NO3)2 solution, adjust the pH of the solution to 4.5, and place it in a constant temperature pot at 70°C for insulation. Use the pretreated carbon cloth obtained in step S1 as the working electrode, Ag / AgCl (saturated KCl solution) as the reference electrode, and Pt sheet as the counter electrode for electrochemical deposition. Deposition steps: first treat in a constant current mode of -2 mA for 15 S, then deposit in a constant potential mode of -1V for 30 min, and finally dry in an oven at 60°C for 3 h to obtain a carbon cloth with a ZnO nanolayer deposited.

[0030] Preparation of S3, ZnO / CdS composite films The carbon cloth with ZnO film deposited on it prepared in step S2 was placed in the middle of the spin coater, and 100 μL of 30 mM Cd(CH3COO)2·2H2O ethanol solution A 30S was dripped at 2000 rpm, repeated twice, and then dried in a 60°C oven for 5 min; after taking it out, 100 μL of 30 mM Na2S·9H2O methanol solution B 30 S was dripped at 2000 rpm, repeated twice, and then dried in a 60°C oven for 5 min. The above entire drip coating process is one cycle, and the cycle is repeated six times to obtain a dense, uniform and flexible ZnO / CdS composite nanofilm.

[0031] Example 2 This embodiment provides a flexible ZnO / CdS composite nanofilm for photocathode protection, and the specific preparation method is as follows: S1. Pretreatment of carbon cloth The carbon cloth with a thickness of 0.35 mm was cut into rectangular carbon cloth sheets of 20*10 mm, and then soaked in a mixed solution of deionized water and anhydrous ethanol with a volume ratio of 7:3 at 70°C for 5 hours, and finally dried at 60°C. The dried carbon cloth was soaked in a mixed solution of 8% nitric acid and 8% sulfuric acid with a volume ratio of 3:1 at 70°C for 2 hours to complete the carbon cloth pretreatment.

[0032] Preparation of S2 and ZnO thin films Take 60mL of 0.005M Zn(NO3)2 solution, adjust the pH of the solution to 5, and place it in a constant temperature pot at 80℃ for insulation. Use the pretreated carbon cloth obtained in step S1 as the working electrode, Ag / AgCl (saturated KCl solution) as the reference electrode, and Pt sheet as the counter electrode for electrochemical deposition. Deposition steps: first treat in a constant current mode of -2 mA for 15 S, then deposit in a constant potential mode of -1 V for 20 minutes, and finally dry in an oven at 60℃ for 3 h to obtain a carbon cloth with a ZnO nanolayer deposited.

[0033] Preparation of S3, ZnO / CdS composite films The carbon cloth with ZnO film deposited on it prepared in step S2 was placed in the middle of the spin coater, and 100 μL of 35 mM Cd(CH3COO)2·2H2O ethanol solution A 30S was dripped at 2500 rpm, repeated twice, and then dried in a 60°C oven for 5 min; after taking it out, 100 μL of 35 mM Na2S·9H2O methanol solution B 30 S was dripped at 2500 rpm, repeated twice, and then dried in a 60°C oven for 5 min. The above entire drip coating process is one cycle, and the cycle is repeated six times to obtain a dense, uniform and flexible ZnO / CdS composite nanofilm.

[0034] Example 3 This embodiment provides a flexible ZnO / CdS composite nanofilm for photocathode protection, and the specific preparation method is as follows: S1. Pretreatment of carbon cloth The carbon cloth was cut into rectangular carbon cloth sheets of 20*10 mm, and then soaked in a mixed solution of deionized water and anhydrous ethanol with a volume ratio of 7:3 at 80°C for 3 h, and finally dried at 60°C. The dried carbon cloth was soaked in a mixed solution of 12% nitric acid and 12% sulfuric acid with a volume ratio of 3:1 at 80°C for 1 h to complete the carbon cloth pretreatment.

[0035] Preparation of S2 and ZnO thin films Take 60 mL of 0.01 M Zn(NO3)2 solution, adjust the pH of the solution to 4.5, and place it in a constant temperature pot at 70°C for insulation. Use the pretreated carbon cloth obtained in step S1 as the working electrode, Ag / AgCl (saturated KCl solution) as the reference electrode, and Pt sheet as the counter electrode for electrochemical deposition. Deposition steps: first treat in a constant current mode of -2 mA for 15 S, then deposit in a constant potential mode of -1V for 30 min, and finally dry in an oven at 60°C for 3 h to obtain a carbon cloth with a ZnO nanolayer deposited.

[0036] Preparation of S3, ZnO / CdS composite films The carbon cloth with ZnO film deposited on it prepared in step S2 was placed in the middle of the spin coater, and 100 μL of 25 mM Cd(CH3COO)2·2H2O ethanol solution A 30 S was dripped at 1500 rpm, repeated twice, and then dried in a 60°C oven for 5 min; after taking it out, 100 μL of 25 mM Na2S·9H2O methanol solution B 30 S was dripped at 1500 rpm, repeated twice, and then dried in a 60°C oven for 5 min. The above entire drip coating process is one cycle, and the cycle is repeated six times to obtain a dense, uniform and flexible ZnO / CdS composite nanofilm.

[0037] Comparative Example 1 This comparative example provides a flexible ZnO / CdS composite nanofilm for photocathode protection. The specific preparation method is basically the same as that of Example 1, except that the carbon cloth in step S1 is not treated and the subsequent steps are directly performed, while the rest remain unchanged.

[0038] During the experiment, it was found that it was impossible to form a composite nanofilm. The possible reason is that the untreated carbon cloth is not hydrophilic and it is difficult to deposit nano ZnO in the Zn (NO3) 2 aqueous solution.

[0039] Comparative Example 2 This comparative example provides a flexible ZnO / CdS composite nanofilm for photocathode protection. The specific preparation method is basically the same as that in Example 1, except that: in the deposition step in the preparation of the ZnO film in step S2, first treat it in a constant current mode of -2 mA for 15S, then deposit it in a constant potential mode of -0.8 V for 20 min, and the rest remain unchanged.

[0040] Comparative Example 3 This comparative example provides a flexible ZnO / CdS composite nanofilm for photocathode protection. The specific preparation method is basically the same as that in Example 1, except that: in step S3, CdS is replaced with Bi2S3, the bismuth source in the Bi2S3 nanolayer is 20 mM Bi(NO3)3·5H2O in ethylene glycol solution A, and the sulfur source is 30 mM Na2S·9H2O in methanol solution B, and the rest remain unchanged.

[0041] Comparative Example 4 This comparative example provides a flexible ZnO / CdS composite nanofilm for photocathode protection. The specific preparation method is basically the same as that in Example 1, except that in step S3, ethanol solution A and methanol solution B are both dripped twice, the entire dripping process is cycled twice, and the rest remains unchanged.

[0042] Furthermore, in order to understand the performance of the composite nanofilm prepared above, the composite nanofilms prepared in Example 1 and Comparative Examples 2-4 were selected and the following experiments were conducted: The prepared composite nanofilm was used as a photoanode and placed in a photoelectrolysis cell of a mixed solution of 0.1 M Na2S and 0.2 M NaOH. The protected 304 stainless steel was used as a working electrode and placed in a corrosion electrolysis cell. A Pt sheet was used as a counter electrode, Ag / AgCl (saturated KCl solution) was used as a reference electrode, and 3.5wt% NaCl was used as the corrosion electrolysis cell solution. The corrosion electrolysis cell and the photoelectrolysis cell were connected through a cation exchange membrane. A 300 W xenon lamp equipped with a ≥420 nm filter was used as a simulated solar light source. The number and time of shutter opening and closing were set to simulate the sunlight illumination-darkness conditions. The potential and current changes under light and darkness after the photoanode was coupled to the metal were tested using an electrochemical workstation. See the schematic diagram of the experiment. Figure 3 , see the specific test results Figure 5-8 .

[0043] Depend on Figure 5 It can be seen that: Figure 5(a) It can be seen that the potential of the coupled 304 stainless steel under light drops to -1220 mV, which is much lower than the self-corrosion potential of 304 stainless steel (-230 mV). After turning off the light source, the coupled potential slowly rises to -460 mV, but is still lower than the self-corrosion potential of 304 stainless steel. When the light is irradiated again, the potential drops rapidly to below -1221 mV, indicating that the composite film has good stability. Figure 5 (b) It can be seen that the photocurrent density generated by the photoanode after illumination is 1404 μA / cm 2 This indicates that the composite material has excellent photoelectric cathode protection performance.

[0044] Depend on Figure 6 It can be seen (Comparative Example 2): Figure 6 (a) It can be seen that the potential of the coupled 304 stainless steel under light drops to -724 mV, which is much lower than the self-corrosion potential of 304 stainless steel (-230 mV). After turning off the light source, the coupled potential slowly rises to -503 mV, but is still lower than the self-corrosion potential of 304 stainless steel. When the light is irradiated again, the potential drops rapidly to below -724 mV, indicating that the composite film has good stability. Figure 6 (b) It can be seen that the photocurrent density generated by the photoanode after illumination is 80 μA / cm 2 This shows that the deposition of 20 min in the constant potential mode at -0.8 V can also prepare nano ZnO thin film, but the ZnO crystal has a small specific surface area, which is not conducive to the attachment of CdS nanoparticles and the construction of heterojunction, so the performance of photocathode protection does not achieve the best effect.

[0045] Depend on Figure 7 It can be seen (Comparative Example 3): from Figure 7 (a) It can be seen that the potential of the coupled 304 stainless steel under light drops to -790 mV, which is lower than the self-corrosion potential of 304 stainless steel (-230 mV). After turning off the light source, the coupled potential slowly rises to -450 mV, but is still lower than the self-corrosion potential of 304 stainless steel. When the light is irradiated again, the potential drops rapidly to below -810 mV, showing good stability. Figure 7 (b) It can be seen that the photocurrent density generated by the photoanode after illumination is 62 μA / cm 2 However, the coupling potential drop and the generated photocurrent density are not as good as those of ZnO / CdS nanocomposite film.

[0046] Depend on Figure 8 It can be seen (Comparative Example 4): Figure 8(a) It can be seen that the potential of the coupled 304 stainless steel under light drops to -697 mV, which is also much lower than the self-corrosion potential of 304 stainless steel (-230 mV). After turning off the light source, the coupled potential slowly rises to -490 mV, but is still lower than the self-corrosion potential of 304 stainless steel. When the light is irradiated again, the potential drops rapidly to below -697 mV, indicating that the composite film has good stability. Figure 8 (b) It can be seen that the photocurrent density generated by the photoanode after illumination is 60 μA / cm 2 This indicates that when the number of cycles in the second step deposition is small, the prepared CdS nanolayer is thinner, the absorption and utilization rate of sunlight is poor, and therefore the photocathode protection effect is also slightly poor.

[0047] From the above experiments, it can be seen that the light absorption range of the composite nanofilm prepared in this application is extended to the visible light region compared with pure ZnO (light absorption range 200-370 nm). Its soft texture is more suitable for different operating scenarios than traditional rigid photoanodes. The potential of the coated steel electrode in the corrosion electrolytic cell coupled with it drops to below -1200 mV, which is significantly lower than its self-corrosion potential.

[0048] The specific raw materials not described in the present invention are all existing materials and can be directly purchased from the market.

[0049] The above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A flexible ZnO / CdS composite nanofilm for photocathode protection, characterized in that: The composite nanofilm comprises a carbon cloth substrate, a ZnO nanolayer, and a CdS nanolayer; The carbon cloth substrate needs to be pretreated: first, it is soaked in a mixed solution of deionized water and anhydrous ethanol, then subjected to liquid phase oxidation hydrophilic treatment, and then dried for standby use.

2. The composite nanofilm according to claim 1, characterized in that: The carbon cloth substrate has a thickness of 0.35-0.4 mm; The volume ratio of deionized water to anhydrous ethanol is 7:3, and the soaking time is 3-5 hours; Liquid phase oxidation hydrophilic treatment steps: soak for 1 to 2 hours at 70 to 80°C in a mixed solution of nitric acid and sulfuric acid with a volume ratio of 3:1 and a mass fraction of 8% to 12%.

3. The composite nanofilm according to claim 1, characterized in that: The ZnO nanolayer is prepared from a Zn(NO3)2 solution by using an electrochemical deposition process.

4. The composite nanofilm according to claim 1, characterized in that: The CdS nanolayer is prepared by using an SC-SILAR process with an ethanol solution A of Cd(CH3COO)2·2H2O as a cadmium source and a methanol solution B of Na2S·9H2O as a sulfur source.

5. A method for preparing the composite nanofilm according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, taking Zn(NO3)2 solution, using the pretreated carbon cloth substrate as the working electrode, the platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode for electrochemical deposition, and drying after the deposition is completed to obtain a carbon cloth with a ZnO nanolayer deposited; S2. Place the carbon cloth with the ZnO nanolayer in the middle of the spin coater, apply ethanol solution A dropwise, dry, then apply methanol solution B dropwise, and dry to obtain a flexible ZnO / CdS composite nanofilm.

6. The method according to claim 5, characterized in that The concentration of the Zn(NO3)2 solution is 0.005~0.01 M, and the pH is 4.5~5; Electrochemical deposition process: first treat in constant current mode of -2 mA for 15 S, then deposit in constant potential mode of -1 V for 20~30 min, and the electrodeposition temperature is 60~80℃.

7. The method according to claim 5, characterized in that In step S2, the concentration of Cd(CH3COO)2·2H2O in the ethanol solution A is 25-35 mM; the concentration of Na2S·9H2O in the methanol solution B is 25-35 mM.

8. The method according to claim 5, characterized in that The spin coater speed is 1500-2500 rpm; The drop-coating volume of ethanol solution A and methanol solution B was 80-120 μL, the drop-coating time was 25-35 s, and the drop-coating times were 2 times; The entire coating and drying process cycle is repeated 6 times.

9. The method according to claim 5, characterized in that The drying conditions in step S1 are as follows: temperature 60°C, time 2.5-3.5 h; The drying conditions in step S2 are the same for the two dryings: temperature 60°C, time 3-7 min.

10. Use of the flexible ZnO / CdS composite nanofilm according to claim 1 in photocathode protection.

Citation Information

Patent Citations

  • AgInS2 / graphene / TiO2 nanocomposite film photoanode for photogenerated cathode protection, its preparation and application

    CN109735847B

  • Preparation method of Si-TiO2 photogenerated cathodic protection coating

    CN109913859A

  • Graphite phase carbon nitride@graphene composite film photo-anode for photo-induced cathodic protection

    CN111962083A